Dynamics of phosphorus fixation in selected tea cropped soils on the Mambilla Plateau in Taraba State, Nigeria - E. Aikpokpodion, Paul (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Phosphorus deficiency in tea grown soils is a major factor responsible for the low yield of tea in Nigeria. Fertilizer application is always a remedy for nutrient deficiency in agricultural soils. High P-fixation in tea soils is mainly due to inherent soil acidity, clay content, hydrated oxides of aluminum and iron. This research aims to understand the fate of phosphorus, P-fractional recovery and P-fixation in tea grown soils is required. Methods: Soil samples were obtained from selected tea farms in Nguroje and Kusuku communities on the Mambilla plateau. The samples were incubated with known concentrations of phosphorus and P-fractional recovery was carried out at 3, 15, 30, 45 and 60 days of incubation. Results: Results showed that, phosphorus fixation was intense in both soils within the first 15 days of incubation. P –fixation was higher in Kusuku soil than Nguroje soil in the first 15 days. Fixation was more progressive in Nguroje soil while it reached a climax in Kusuku soil within the first 15 days of soil incubation before desorption of fixed phosphorus began. Clay, Al, Fe, Ca and Mg contents were the soil properties that contributed to phosphorus fixation in the investigated soils. Conclusion: The fact that, fixed phosphorus was gradually recovered was an indication that, P-fixation in tea grown soils on the Mambilla plateau was temporal and not permanent.